2002
DOI: 10.1176/appi.ps.53.12.1563
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care for Latinos: Translating Research Into Action: Reducing Disparities in Mental Health Care for Mexican Americans

Abstract: This article describes a case study in which epidemiologic research findings were translated for multiple stakeholders and applied to reduce disparities in mental health services for Mexican Americans in Fresno County, California. The aims of this evidence-based process were to educate the community and mobilize action, translate research for multiple stakeholders to inform practitioners and policy makers about the need for improved mental health care for minorities, and effect regional policy changes to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…The traditional view of the acculturative process suggests that as individuals become more assimilated they begin to adopt customs and behaviors common to the new culture. This may have particular significance for substance use since the rates for general populations in Hispanic countries are substantially lower than those within the United States (Aguilar-Gaxiola et al 2002). Other research has suggested that this may be due, in part, to greater exposure and easier access to drugs and alcohol in the U.S. (Gil et al 2000).…”
Section: Acculturation and Hispanic Drug Usementioning
confidence: 99%
See 1 more Smart Citation
“…The traditional view of the acculturative process suggests that as individuals become more assimilated they begin to adopt customs and behaviors common to the new culture. This may have particular significance for substance use since the rates for general populations in Hispanic countries are substantially lower than those within the United States (Aguilar-Gaxiola et al 2002). Other research has suggested that this may be due, in part, to greater exposure and easier access to drugs and alcohol in the U.S. (Gil et al 2000).…”
Section: Acculturation and Hispanic Drug Usementioning
confidence: 99%
“…This may be particularly relevant for drug use given the comparative proclivity for substance use and abuse in the United States relative to Latin American countries (Aguilar-Gaxiola et al 2002).…”
mentioning
confidence: 99%
“…Parallel to this growth will be an increase in the number of Latinos with chronic psychosis, making it necessary for healthcare providers to increase access to effective services. However, data suggests there are disparities in the use of mental health services in the Latino population compared to non-Latino Whites 3, 4 , perhaps due to barriers to initial service use (e.g., language capabilities, availability of services in one's community, and income level) 3 , or to a reduced likelihood of continued service use due to Latinos' perception that the quality of care they received was poor or not relevant to their specific circumstances 5,6 . Therefore, to make healthcare services accessible and meaningful to Latino clients, healthcare providers need to address these barriers to quality care.…”
Section: Introductionmentioning
confidence: 99%
“…The research that has attempted to understand the disparities in mental health care for Latinos has led to a variety of explanations for why Latinos may receive inadequate mental health services (Aguilar-Gaxiola et al, 2002;Alegría et al, 2002;Cabassas et al, 2006;Johnson, Saha, Arbelaez, Beach, & Cooper, 2004;Lopez, 2002;Vega & Lopez, 2001). Some of the explanations have focused on system-level barriers (e.g., lack of Spanish-speaking service providers, inadequate training in the delivery of culturally competent services), while other explanations have focused on patient-level barriers (e.g., different views of mental health and mental health treatment, concern regarding stigma, logistical problems associated with poverty).…”
Section: Introductionmentioning
confidence: 99%